In-hospital, Thirty-day, One-year Mortality and Risk Factors of Mortality in the Elderly After Hip Fracture Surgery - Ryden, Patcharin; Maungrung, Monrudee (Srinagarind Medical Journal, 2021)
บทคัดย่อ ภาวะกระดูกหักรอบข้อสะโพก จากกระดูกพรุนพบได้บ่อยและมีภาวะแทรกซ้อนทางคลินิกมากที่สุด อุบัติการณ์ของกระดูกหักรอบข้อสะโพกเพิ่มขึ้นในประชากรผู้สูงอายุ มีความสัมพันธ์กับอัตราการเสียชีวิตที่มากขึ้น ความสามารถในการเคลื่อนไหวและการทำกิจวัตรประจำวันลดลง การรักษานิยมใช้การผ่าตัดเพื่อให้ผู้ป่วยมีการเคลื่อนไหวได้เร็วขึ้น เพื่อป้องกันภาวะแทรกซ้อนจากการนอนติดเตียง อัตราการเสียชีวิตของผู้ป่วยสูงอายุภายหลังการผ่าตัดรักษากระดูกหักรอบข้อสะโพกยังคงสูง ปัจจัยเสี่ยงที่มีความสัมพันธ์กับการเสียชีวิต ได้แก่ อายุที่มากขึ้น เพศชาย โรคร่วม การเคลื่อนไหวน้อยลงในผู้สุงอายุ การรับรู้ลดลง รวมทั้งระยะเวลารอการผ่าตัดล่าช้า บทความนี้มีวัตถุประสงค์เพื่อวิเคราะห์อัตราการเสียชีวิตในโรงพยาบาล เสียชีวิตใน 30 วัน และ 1 ปี และปัจจัยเสี่ยงการเสียชีวิต ในผู้ป่วยสูงอายุที่ได้รับการผ่าตัดหลังกระดูกหักรอบข้อสะโพก เพื่อให้บุคลากรทางการแพทย์เข้าใจสถานการณ์ และระมัดระวังในการดูแลผู้ป่วยกลุ่มนี้มากขึ้น อีกทั้งการระบาดของโรคโควิด-19 ในปัจจุบันได้ส่งผลกระทบต่อกลุ่มประชากรที่มีความเสี่ยงสูงนี้อย่างมาก ซึ่งบทความนี้ยังได้ทบทวนวรรณกรรมที่รายงานอัตราการเสียชีวิตใน 30 วันในผู้ป่วยสูงอายุที่มีกระดูกหักรอบข้อสะโพกกลุ่มนี้ไว้ด้วยเช่นกัน คำสำคัญ : กระดูกหักรอบข้อสะโพกในผู้สูงอายุ; อัตราการเสียชีวิตภายหลังการผ่าตัด; อัตราการเสียชีวิตในโรงพยาบาล; อัตราการเสียชีวิตใน 30 วัน; อัตราการเสียชีวิตใน 1 ปี; ปัจจัยเสี่ยงการเสียชีวิตในผู้ป่วยกระดูกหักรอบข้อสะโพก ABSTRACT Hip fracture is a common osteoporotic fracture with the most clinical complications. The incidence of hip fractures is increasing within the aging population. Hip fractures are associated with increased mortality and loss of ability to perform daily life activities. Surgical intervention is favored in these patients for early mobilization to prevent complications associated with prolonged bed rest. Mortality in elderly patients after the surgical treatment of hip fractures remains high. The risk factors were associated with increased mortality in hip fracture patients including advanced age, male gender, clinical comorbidities, decreased movement in elderly patients, cognitive impairment and delayed time to surgery. The aim of this article is to analyses mortality in-hospital, 30-day, 1-year mortality and risk factors of mortality in elderly patients who underwent surgery following a hip fracture so it could help medical care personnel realize the situation and more beware in this group of patients. Moreover, the current COVID-19 pandemic has affected substantially this high-risk population group. This article has also reviewed the affected of 30-day mortality of hip fracture in the elderly patients. Keywords: Hip fractures in elderly; mortality after surgery; in-hospital mortality; 30-day mortality; 1-year mortality; risk factors of mortality in hip fracture patients